Enjolras Vampré and the character of Les Misérables - Alex Tiburtino Meira; Gustavo Leite Franklin; Maria Luísa Pacífico Brandão Meira; Isabella Araújo Mota; Egberto Reis Barbosa; Hélio Afonso Ghizoni Teive (Arquivos de Neuro-Psiquiatria)
ABSTRACT Enjolras Vampré (1885-1938) was one of the pioneering neurologists in Brazil whose name is a tribute to one of the characters of the book Les Misérables (1862), written by Victor Hugo (1802-1885). In this article, the authors point out evidence that the coincident names were not just a matter of homage, and even more so, the life of Dr. Enjolras had many similarities with the interesting character.